2018
DOI: 10.1016/j.expneurol.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E as a novel therapeutic neuroprotection target after traumatic spinal cord injury

Abstract: Apolipoprotein E (apoE), a plasma lipoprotein well known for its important role in lipid and cholesterol metabolism, has also been implicated in many neurological diseases. In this study, we examined the effect of apoE on the pathophysiology of traumatic spinal cord injury (SCI). ApoE-deficient mutant (apoE−/−) and wild-type mice received a T9 moderate contusion SCI and were evaluated using histological and behavioral analyses after injury. At 3 days after injury, the permeability of spinal cord-blood-barrier,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 99 publications
3
21
0
Order By: Relevance
“…The ability of CARPs to reduce cell surface levels of NR2B is at least one mechanism whereby the peptides reduce the damaging effects of glutamate-induced excitotoxicity. Furthermore, based on other CARP neuroprotection studies, which include many TAT-fused putative neuroprotective peptides, they have been demonstrated to down-regulate and/or antagonise other neuronal calcium channels/receptors [ 12 , 25 34 ], activate pro-survival signalling pathways in neurons [ 34 36 ], assist in maintaining neuronal mitochondrial integrity [ 11 , 37 ] and reduce neuro-inflammation [ 38 , 39 ]. In addition, it is likely that the ability of CARPs to exert their neuroprotective actions is mediated in part, to the positively charged guanidino group that is only present in arginine residues [ 2 , 3 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ability of CARPs to reduce cell surface levels of NR2B is at least one mechanism whereby the peptides reduce the damaging effects of glutamate-induced excitotoxicity. Furthermore, based on other CARP neuroprotection studies, which include many TAT-fused putative neuroprotective peptides, they have been demonstrated to down-regulate and/or antagonise other neuronal calcium channels/receptors [ 12 , 25 34 ], activate pro-survival signalling pathways in neurons [ 34 36 ], assist in maintaining neuronal mitochondrial integrity [ 11 , 37 ] and reduce neuro-inflammation [ 38 , 39 ]. In addition, it is likely that the ability of CARPs to exert their neuroprotective actions is mediated in part, to the positively charged guanidino group that is only present in arginine residues [ 2 , 3 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, APOE mimetic peptide significantly suppressed microglial activation in rats with SCI. Conversely, the excessive inflammation may be caused by the increased permeability of BSCB leading to the influx of inflammatory cells in peripheral blood in Apoe −/− mice after SCI (Wang et al, 2014 ; Cheng et al, 2018 ). Moreover, Apoe −/− mice showed that increased oxidative stress caused an exaggerated neuronal deposition and contributed to the neurodegenerative processes (Nuriel et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…AMPAR, NCX, TRPV1, CaV2.2, CaV3.3) that may exacerbate excitotoxic ionic disturbances in the brain following stroke [221][222][223][224][225][226][227][228][229][230][231], and is one likely mechanism whereby the peptides reduce the damaging effects of glutamate-induced excitotoxicity. In addition to the confirmed neuroprotective properties of CARPs, they possess other properties that may be beneficial following stroke; they induce the internalization of cell surface TNF receptors [231], scavenge free radicals and reduce lipid peroxidation [189][190][191][192], inhibit the activity of the proteasome [232][233][234], reduce inflammatory responses [235][236][237][238][239][240][241], activate pro-cell survival signalling [218,229,242], and inhibit pro-protein convertases that activate matrix metalloproteinases [243][244][245]. In vitro studies examining the cytoprotective properties of SS-peptides have revealed several potential mechanisms of actions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%